2020
DOI: 10.3390/nu12030824
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a High-Fat Diet on the Fatty Acid Composition in the Hearts of Mice

Abstract: The Western diet can lead to alterations in cardiac function and increase cardiovascular risk, which can be reproduced in animal models by implementing a high-fat diet (HFD). However, the mechanism of these alterations is not fully understood and may be dependent on alterations in heart lipid composition. The aim of this study was to evaluate the effect of an HFD on the fatty acid (FA) composition of total lipids, as well as of various lipid fractions in the heart, and on heart function. C57BL/6 mice were fed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
9
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 109 publications
6
9
0
Order By: Relevance
“…As expected, increased cardiac TG levels were also observed [63]. In heart tissue of mice fed a high fat diet, increases in polyunsaturated fatty acyl chains were observed in ceramides, glycosphingolipids, and sphingomyelins whereas decreases in monounsaturated fatty acyl chains were observed in phospholipids and sphingomyelins [64]. In another study, researchers determined that feeding mice a diet enriched in polyunsaturated fatty acids (arachidonic acid, eicosapentaenoic acid, or docosahexaenoic acid supplemented) for two weeks decreased cardiac phospholipids containing linoleic acid when compared to control mice on a fish meal free diet [65].…”
Section: Cardiac Lipid Profiles In Animal Models Of Obesitysupporting
confidence: 74%
“…As expected, increased cardiac TG levels were also observed [63]. In heart tissue of mice fed a high fat diet, increases in polyunsaturated fatty acyl chains were observed in ceramides, glycosphingolipids, and sphingomyelins whereas decreases in monounsaturated fatty acyl chains were observed in phospholipids and sphingomyelins [64]. In another study, researchers determined that feeding mice a diet enriched in polyunsaturated fatty acids (arachidonic acid, eicosapentaenoic acid, or docosahexaenoic acid supplemented) for two weeks decreased cardiac phospholipids containing linoleic acid when compared to control mice on a fish meal free diet [65].…”
Section: Cardiac Lipid Profiles In Animal Models Of Obesitysupporting
confidence: 74%
“…This is particularly interesting in view of recent data suggesting that cytochrome P450 (CYP) enzymes more efficiently convert n-3 acids to epoxy and hydroxy metabolites that potentially mediate beneficial cardiovascular effects [ 32 ]. The increase of sHE in animals fed the SFA diet was not surprising and was consistent with the results of Pakiet et al (2020), who have reported an increase in cardiac PUFA concentration in mice fed a HFD rich in SFA and MUFA [ 39 ].…”
Section: Discussionsupporting
confidence: 89%
“…2 c, TG levels were 378% higher in the liver of HFHSD mice compared to SD mice, but unaltered in the other organs. The difference between NMR and triglycerides quantification in the skeletal muscles, and to a lesser extent in the heart, may indicate the accumulation of free fatty acids in these organs, which can be detected by NMR only, a phenomenon already observed with high-fat diets 19 .…”
Section: Resultsmentioning
confidence: 91%